Watershed as a scale of planning and community governance: The case of the Tiburtino stream in São Paulo - Lima, Renata Priore; Silva, Luciano Abbamonte da (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This paper delves into the integration of watershed management into territorial planning and community governance, focusing on the evolution of the São Crispim Square Preservation Movement and the Subgroup for Sustainable Drainage of the Tiburtino Stream with Nature-Based Solutions within CADES Lapa. It also examines the processes leading to the formulation of guidelines for a prospective drainage plan for the basin, drawing from both technical-political initiatives along with the experiential knowledge of residents and stakeholders. The methodological framework encompasses a literature review, urban characterization of the Tiburtino basin, synthesis of key steps in local social movements, examination of relevant legislation and urban plans, compilation of civil society actions, and categorization of recommendations for the development of a sustainable drainage plan. The outcome offers a historical account of the social movement advocating for São Crispim Square’s preservation and introduces possible urban intervention guidelines for implementing Nature-based Solutions (NbSs) in the Tiburtino basin, including Sustainable Drainage Systems (SuDS). This attempt aims to guide cities in adapting to and mitigating the impacts of climate change, promoting urban, environmental, and water resilience in alignment with sustainable development objectives.